Britain in "decline"?. Vol. 19 - Cannadine, David, 1950- (Waco, Tex. : Markham Press Fund, 1998)
In this elegantly written work, Cannadine neatly captures the essence of and makes his own provocative contributions to a major historiographical controversy over the decline of Britain, and personalizes it through penetrating portraits of three seemingly unrelated political leaders: Joseph Chamberlain, Winston Churchill, and Margaret Thatcher. The argument that British decline was and is inevitable -- but also that the decline is geopolitical and not personal in terms of individual standards of living -- is a convincing one, and Cannadine's ability to juxtapose this decline against the aggressive policies of these three twentieth-century leaden adds an element of irony to his tale. Included in this work is a thoughtful discussion of how historical writing is shaped by and perhaps also shapes its environment. Cannadine offers suggestions on how we might go about rewriting the history of Britain as we enter a new century and a new millennium. These insights and comments are particularly important as they come from the General Editor of the new Penguin History of Britain series, through which Cannadine's theories about and approaches to the writing of history are being put into practice. While the work is limited to a discussion of British history, the observations Cannadine offers might equally well be applied students of American or other national histories. -- Provided by publisher.
Baylor University, Waco Texas, April 7-8, 1997.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Great Britain -- Politics and government -- 20th century; Great Britain -- History -- 20th century; Great Britain -- Historiography; Grande-Bretagne -- Politique et gouvernement -- 20e siècle.; Grande-Bretagne -- Histoire -- 20e siècle.; HISTORY; Historiography; Politics and government; Great Britain; 1900-1999; History